ACI‐24 in adults with Down syndrome: Results of a phase 1b, randomized, placebo‐controlled study. (31st December 2021) - Rafii, Michael S; Sol, Olivier; Mobley, William C; Skotko, Brian G.; Burke, Anna D; Sabbagh, Marwan N.; Yuan, Shauna; Rissman, Robert A.; Delpretti, Saskia; Beth, Greg; Gray, Julian JG; Melo dos Santos, Antonio; et al.
Abstract: Background: The APP gene is located on chromosome 21 and thought to lead to overproduction of beta‐amyloid (Aβ) in persons with trisomy 21 (Down syndrome, DS). As a result, individuals with DS are at high risk for developing Alzheimer's disease (AD). ACI‐24 is a liposomal, T‐cell independent, anti‐Aβ vaccine which was assessed in a world's first clinical phase 1b study in adults with DS. Method: The primary objectives of this randomized, double‐blind, placebo‐controlled, dose‐escalation, phase Ib multi‐center study were to assess the safety and tolerability of ACI‐24 in adults aged 25‐45 years with DS and its effect on the induction of serum anti‐Aβ antibody titers. The secondary objectives were to explore the effect of ACI‐24 on cognition, behavior, AD biomarkers, T‐cell activation, and brain volumes assessed by MRI. Participants received subcutaneous injections of ACI‐24 (300 µg or 1000 µg) or placebo (3:1 ratio) at different timepoints up to week 48 before entering a 48‐week safety follow‐up period. Result: Sixteen participants (9F/7M; mean age 32.9 [25‐41]) were randomized into 2 dose‐level cohorts (n=8 each; 6 ACI‐24 and 2 placebo). Treatment compliance was 100%. The safety and tolerability were very good with no serious adverse events reported and no withdrawals due to adverse events. Most adverse events were mild in intensity and unrelated or unlikely related to ACI‐24. No amyloid‐related imaging abnormalities (ARIA) or changes in markers of CNS inflammation were observed. Increases in anti‐Aβ antibody titers were observed in selected participants in both treatment arms receiving ACI‐24 as compared to placebo. In addition, an increase in plasma Aβ1‐40 and Aβ1‐42 levels compared to placebo was observed in active groups. As expected, no consistent changes between treatment and placebo groups were observed in other biomarkers or clinical measures in this small study. Conclusion: ACI‐24 was safe and well‐tolerated in adults with DS. Evidence of immunogenicity was observed with this T‐cell independent vaccine along with pharmacodynamic and target engagement effects as measured by an increase in plasma Aβ 1‐40 and Aβ 1‐42 levels in treated groups as compared to placebo. These results support the pursuance of an accelerated clinical development with an optimized formulation of ACI‐24.